Expert Analysis: The Reciprocal Relationship between Sports Gambling and Fantasy Football on Television. Issue 1 (14th July 2021) - Kupfer, Alexander; Anderson, Jamie
Abstract: Television coverage of football gambling established the industrial preconditions within sports media for fantasy sports coverage to emerge and proliferate. Coverage of gambling and fantasy sport encourages active, dedicated consumptive behaviour and participation from audiences. The popularization of content devoted to these activities illuminates key tensions marking the discourses around both sports betting and fantasy football since leagues like the NFL have distanced themselves from gambling. Nonetheless, paratextual television programmes dedicated to sports gambling developed the discursive frameworks that define sports betting and fantasy football as skill- and research-based pastimes. Gambling experts, especially Jimmy 'the Greek' Snyder, facilitated the emergence of contemporary 'fantasy gurus' like ESPN's Matthew Berry. These on-air experts brand themselves through a particular combination of statistical analysis, commentary, and humor. Both Snyder and Berry analyze statistical data and trends to offer viewers reasons to put specific players in weekly fantasy lineups or bet a certain way. Historically, sports betting and fantasy football programmes have had a mutually-beneficial relationship with media industries. This relationship reveals the process by which marginal forms of sports media can move from the periphery to the center of fan culture.